Molecular Detection of Mycobacterium tuberculosis in Urinary Bladder FFPET Samples Could be a Proposed Specific Entity Of Bladder Carcinoma. - Hashim Raheem Tarish; Asaad Aljanabi; Zina Mohammed Abdul-Hussein (Kufa Journal for Nursing Sciences)
Background: Bladder cancer is one of the most common human cancers in Iraq and the world. While smoking, age, gender, and occupational exposure to aromatic amines are the most prominent among the risk factors identified, long term Inflammation and chronic infection may largely play some role in urinary bladder cancer (UBC) development. The association between bacterial inflammation and cancer appears to be stronger especially in chronic type of infection, many studies mentioned the role of chronic Escherichia coli (E. coli) infection and UBC but there was no study mentioned the role of chronic Mycobacterium tuberculosis (MTB) infection in association with UBC. There are many cellular and immune responses that occur during chronic Mycobacterial infection such as irritation, long term inflammatory cytokine production and DNA damaging due to bacterial metabolic products are some factors that may give chance for UB neoplastic changes. In the present study we worked on urinary bladder cancer and noncancerous Formalin-Fixed Paraffin Embedded (FFPE) Tissue specimens of Iraqi patients, the current study used polymerase chain reaction (PCR) for detection of Mycobacterium tuberculosis genome.